Chronic Airflow Limitation, Lower Respiratory Symptoms, COPD and Chronic Rhinosinusitis in a Middle-Aged Population: The Swedish CArdioPulmonary bioImage Study (SCAPIS). A Link Between the Lower and Upper Airways - Andersson A; Bergqvist J; Schiöler L; Bossios A; Farnebo L; Holmlund T; Janson C; Keceli S; Ljunggren M; Malinovschi A; Memarian E; Nihlén U; et al. (International Journal of COPD)
Anders Andersson,1,2,* Joel Bergqvist,3,4,* Linus Schiöler,5 Apostolos Bossios,6,7 Lovisa Farnebo,8,9 Thorbjörn Holmlund,10 Christer Janson,11 Sumru Keceli,12 Mirjam Ljunggren,11 Andrei Malinovschi,13 Ensieh Memarian,14 Ulf Nihlén,15 Peter M Nilsson,16,17 Ida Pesonen,18,19 Marcus Sjöström,10 Nikolai Stenfors,20 Fredrik Sundbom,11 Mimmi Werner,10 Kjell Torén,5,21 Magnus Sköld,22,23 Johan Hellgren24,25 1COPD Center, Department of Respiratory Medicine and Allergology, Sahlgrenska University Hospital, Gothenburg, Sweden; 2COPD Center, Department of Internal Medicine and Clinical Nutrition, Institute of Medicine, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 3Department of Respiratory Medicine and Allergology, Sahlgrenska University Hospital, Gothenburg, Sweden; 4Centre for Sleep and Wake Disorders, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 5Occupational and Environmental Medicine, School of Public Health and Community Medicine, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 6Karolinska Severe Asthma Center, Department of Respiratory Medicine and Allergy, Karolinska University Hospital, Stockholm, Sweden; 7Division of Lung and Airway Research, Institute of Environmental Medicine, Karolinska Institutet, Stockholm, Sweden; 8Linköping University Faculty of Medicine and Health Sciences, Department of Biomedical and Clinical Sciences, Division of Sensory Organs and Communication, Linköping, Sweden; 9Region Östergötland, Anaesthetics, Operations and Specialty Surgery Center, Department of Otorhinolaryngology, Linköping, Sweden; 10Department of Clinical Sciences, Otorhinolaryngology, Umeå University, Umeå, Sweden; 11Department of Medical Sciences: Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 12Department of Otorhinolaryngology in Linköping, Region Östergötland, Linköping, Sweden; 13Department of Medical Sciences, Clinical Physiology, Uppsala University, Uppsala, Sweden; 14Department of Clinical Sciences, IKVM, Internal Medicine, Lund University, Malmö, Sweden; 15Department of Clinical Sciences Lund, Respiratory Medicine and Allergology, Lund University, Lund, Sweden; 16Department of Clinical Sciences, Lund University, Skåne University Hospital, Malmö, Sweden; 17Clinical Research Unit, Department of Internal Medicine, Skåne University Hospital, Malmö, Sweden; 18Respiratory Medicine Unit, Department of Medicine, Karolinska Institutet, Solna, Stockholm, Sweden; 19Department of Respiratory Medicine and Allergy, Karolinska University Hospital, Stockholm, Sweden; 20Department of Public Health and Clinical Medicine, Umeå University, Umeå, Sweden; 21Department of Occupational and Environmental Medicine, Sahlgrenska University Hospital, Gothenburg, Sweden; 22Department of Respiratory Medicine and Allergy, Karolinska University Hospital Solna, Stockholm, Sweden; 23Respiratory Medicine Unit, Department of Medicine Solna and Center for Molecular Medicine, Karolinska Institutet, Stockholm, Sweden; 24Department of Otorhinolaryngology, Head & Neck Surgery, Sahlgrenska University Hospital, Region Västra Götaland, Gothenburg, Sweden; 25Institute of Clinical Sciences, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden*These authors contributed equally to this workCorrespondence: Anders Andersson, COPD Center, Department of Respiratory Medicine and Allergology, Sahlgrenska University Hospital, Bruna Stråket 11B, Göteborg, 413 46, Sweden, Email Anders.Andersson@lungall.gu.sePurpose: Chronic rhinosinusitis (CRS) is related to asthma and chronic obstructive pulmonary disease (COPD). However, combined data on CRS, pulmonary function, lower airway symptoms, and cigarette smoking from the general population are lacking. The current study investigates the relationships between CRS and chronic airflow limitation (CAL), lower airway symptoms and COPD in a middle-aged population of ever-smokers and never-smokers.Patients and Methods: All subjects from the Swedish CArdioPulmonary bioImage Study (SCAPIS) were included. Subjects underwent spirometry after bronchodilation. Chronic airflow limitation was defined as FEV1/FVC ratio < 0.7. Computed tomography imaging of the thorax was performed to detect the presence of emphysema, and the subjects answered a comprehensive questionnaire on CRS, lower airway symptoms, asthma, chronic bronchitis, and cigarette smoking habits.Results: In total, 30,154 adult subjects in the age range of 50– 64 years were included. The prevalence of CRS was 5.6%. CRS was more-prevalent among subjects in the following categories: CAL (7.6%), lower airway symptoms (15.7%), current smokers (8.2%), asthma (13.6%), never-smokers and ever-smokers with COPD (17.6% and 15.3%, respectively), emphysema (6.7%), and chronic bronchitis (24.5%). In the adjusted regression model, CRS was significantly associated with CAL (OR 1.40), lower airway symptoms (OR 4.59), chronic bronchitis (OR 6.48), asthma (OR 3.08), and COPD (OR 3.10).Conclusion: In this national, randomly chosen population sample of more than 30,000 middle-aged men and women, CRS is associated with CAL, lower airway symptoms, chronic bronchitis, asthma, and COPD. In patients with CRS and in patients with lower airway inflammation, it is important to consider the inflammatory status of the entire airway system.Keywords: asthma, chronic bronchitis, chronic obstructive pulmonary disease, emphysema, CRS, smoking